PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP MINAT BELI PELANGGAN PT. ASTRA OTOPARTS DI JAKARTA UTARA - Nino Nopriandi; Dinda Khasa Aulia (Jurnal Ekonomi dan Industri, 2024)
The purpose to analyze the influence of product quality and price on customer purchase interest in PT. Astra Otoparts Jakarta Utara. The research method uses qualitative and quantitative descriptive analysis, the analysis model used is simultaneous and partially linear regression. The research population is all customers at PT. Astra Otoparts Jakarta Utara. The sampling technique used incidental sampling technique. The results of the research show that in simultaneous or partially ways product quality and price have a positive and significant effect on customer purchase interest in PT. Astra Otoparts Jakarta Utara.